CLINICAL CHARACTERISTICS OF HELICOBACTER PYLORI ASSOCIATED GASTRODUODENAL PATHOLOGY IN CHILDREN (World Bulletin of Public Health, 2022)
In recent years, gastroduodenal pathology, including chronic lesions of the upper gastrointestinal tract in children, has been a serious medical and social problem due to its high prevalence, clinical course, and high risk of early disability. Recently, the traditional understanding of the mechanisms of the formation of chronic pathology of the gastrointestinal tract in both adults and children has changed significantly.